IMPLEMENTASI SOSIALISASI ARTIFICIAL INTELLIGENCE SEBAGAI UPAYA PENINGKATAN LITERASI DIGITAL DI MA MISBAHUL ULUM - Zhatria, Juan; Lestari, Wilda; Suciana, Tharis Ayuh; Utami, Dilla Novitri; Annisa, Annisa; Hidayanti, Wiwin; Rante, Cindra Abraham; Dika, Dika; Ardiansah, Wahyu Dias; Kartini, Kartini; Rahmawati, Hilda (Nindikayla Institute, 2025)
The purpose of this service activity is to improve digital literacy at MA Misbahul Ulum, South Sukamaju District, North Luwu Regency, through socialization regarding the introduction and use of artificial intelligence (AI). The implementation of this socialization activity is carried out through several stages, namely preparation, implementation, and evaluation. At the preparation stage, initial observations were made with interviews with the school, followed by providing material on the basics of AI, the latest AI technology, and its application in daily life. In addition, students are also invited to practice the latest use of AI on mobile devices. The results of this activity showed that students were very enthusiastic and actively participated in the question and answer session, which showed an increase in their understanding of AI concepts and applications, especially in relation to informatics subjects. The evaluation of the program showed that this activity succeeded in increasing students' understanding of digital technology and artificial intelligence. It is hoped that this socialization can be a strong foundation for students to be better prepared to face challenges in the ever-evolving digital era. This program is also expected to contribute to improving digital literacy in the educational environment of North Luwu Regency.